1990
DOI: 10.1121/1.399946
|View full text |Cite
|
Sign up to set email alerts
|

Long isotropic buffer rods

Abstract: Longitudinal acoustic wave measurements performed on isotropic aluminum buffer rods with uniform, notched, and tapered peripheries are presented. The buffer rods considered have diameters between a few and several tens of acoustic wavelengths, and lengths of more than a hundred acoustic wavelengths. The buffer rod with a tapered shape was found to be the most effective for eliminating trailing echoes associated with mode conversion on the outer walls of the rods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The spurious echoes are unwanted, since they interfere with desired signals from an inspected object and make the SNR of the desired echo worse. In our previous work, we found that a taper shape of the buffer rod significantly reduced the trailing echoes [13]. In addition, cladding effectively works on not only reducing the trailing echo but also enhancing the ultrasonic guidance, which results in better SNR [8,9].…”
Section: Imagingmentioning
confidence: 99%
“…The spurious echoes are unwanted, since they interfere with desired signals from an inspected object and make the SNR of the desired echo worse. In our previous work, we found that a taper shape of the buffer rod significantly reduced the trailing echoes [13]. In addition, cladding effectively works on not only reducing the trailing echo but also enhancing the ultrasonic guidance, which results in better SNR [8,9].…”
Section: Imagingmentioning
confidence: 99%
“…These spurious echoes deteriorate the SNR because of their possible interference with the desired signals to be measured. An effective way to reduce these unwanted spurious echoes is to use a tapered buffer rod (7) . Since the reduction of spurious echoes depends on the tapering angle, a proper angle has to be chosen in designing the geometry of the rod.…”
Section: Focused Ultrasonic Sensormentioning
confidence: 99%
“…In the last twenty years, several approaches using the buffer rod technique have been made (2) - (4) . Ultrasonic sensors were developed recently, where clad buffer rods provide superior wave guidance performance of high signal-to-noise ratio at elevated temperatures (5) - (7) . It has been demonstrated that such clad buffer rod can detect silicon carbide particles in molten aluminum in pitch-catch mode (8) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome such difficulty, recently clad waveguides with superior ultrasonic wave guidance and high SNR have been developed. 14,15) Using such clad waveguides, several ultrasonic pulse-echo measurements have been successfully performed for molten Zn, 16) Al 17,18) and Mg 19,20) at temperature up to 800 C.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The concept of an ultrasonic waveguide is a common technique for molten metal measurements. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] This technique is rather classical, but it is still attractive because of its simplicity, robustness and cost effectiveness. In this technique, measurements are made using a waveguide while the probe end is immersed in molten metals.…”
Section: Introductionmentioning
confidence: 99%